The SIJORI cross-border region transnational politics, economics, and culture - Chong, Terence; Hutchinson, Francis E. (Singapore ISEAS-Yusof Ishak Institute e(Baltimore, Md. fProject MUSE, 2016)
Twenty-five years ago, the governments of Singapore, Malaysia, and Indonesia agreed to jointly promote the city-state, the state of Johor in Malaysia, and the Riau Islands in Indonesia. Facilitated by common cultural references, a more distant shared history, and complementary attributes, interactions between the three territories developed quickly. Logistics networks have proliferated and production chains link firms based in one location with affiliates or transport facilities in the other territories. These cross-border links have enabled all three locations to develop their economies and enjoy rising standards of living. Initially economic in nature, the interactions between Singapore, Johor, and the Riau Islands have multiplied and grown deeper. Today, people cross the borders to work, go to school, or avail of an increasing range of goods and services. New political, social, and cultural phenomena have developed. Policymakers in the various territories now need to reconcile economic imperatives and issues of identity and sovereignty. Enabled by their proximity and increasing opportunities, families have also begun to straddle borders, with resulting questions about citizenship and belonging. Using the Cross-Border Region framework - which seeks to analyse these three territories as one entity simultaneously divided and bound together by its borders - this book brings together scholars from a range of disciplines. Its 18 chapters and more than 20 maps examine the interaction between Singapore, Johor, and the Riau Islands over the past quarter-century, and seek to shed light on how these territories could develop in the future.
Foreword -- Introduction -- 1. The SIJORI cross-border region : more than a triangle / Francis E. Hutchinson & Terence Chong -- section I. Understanding the Whole -- 2. The population of the SIJORI cross-border region / Aris Ananta -- 3. The SIJORI cross-border region as an economic entity in 1990 and 2012, and perspectives for 2030 / Toh Mun Heng and Jiang Bo -- section II. Policy and politics -- 4. The social construction of comparative advantage and the SIJORI growth triangle / Benjamin Loh -- 5. The political economy of closer relations : a perspective from Singapore / Manu Bhaskaran -- 6. A periphery serving three cores : balancing local, national, and cross-border interests in the Riau Islands / Mulya Amri -- 7. Political contestation in Iskandar Malaysia : views on economic integration during Malaysia's 13th general election / Khor Yu Leng -- 8. Johor survey : interethnic dissonance / Terence Chong -- section III. Cross-border social and cultural communities -- 9. The significance of Riau in SIJORI / Vivienne Wee -- 10. Singaporeans living in Johor and Batam : next-door transnationalism living and border anxiety / Su-Ann Oh and Reema B. Jagtiani -- 11. Singapore Malay family businesses : negotiating Malaysian and Singapore citizenship and national identities / Rizwana Abdul Azeez -- 12. Imaginary frontiers and deferred masculinity : Singapore working-class men in Batam / Terence Chong -- section IV. Formal and informal economies -- 13. The airport and the territory : transnational flows in the Singapore-Johor-Riau cross-border region / Anna Gasco -- 14. Revisiting industrial dynamics in the SIJORI cross-border region : the electronics industry twenty years on / Leo van Grunsven and Francis E. Hutchinson -- 15. Development in Johor and Singapore's water access : challenges and opportunities / J. Jackson Ewing and Pau Khan Khup Hangzo -- 16. The role of ethnic Chinese business networks in the regionalization strategy of Singaporean fish farming firms / Guanie Lim -- 17. Pirates and law enforcement agencies : complex relations across the Malacca Straits / Eric Frécon -- Conclusion -- 18. The SIJORI cross-border region : the whole and sum of its parts / Francis E. Hutchinson.
Includes bibliographical references and index
Keywords: Growth triangles -- Southeast Asia; Southeast Asia -- Economic integration; Riau (Indonesia : Province) -- Foreign economic relations -- Malaysia -- Johor; Riau (Indonesia : Province) -- Foreign economic relations -- Singapore; Johor (Malaysia) -- Foreign economic relations -- Singapore; Singapore -- Foreign economic relations -- Indonesia -- Riau (Province).; Singapore -- Foreign economic relations -- Malaysia -- Johor